The Effects of CaCl2 and Cellulose Concentrations on the Cellulose/PVA/Alginate-Based Filaments Production by Wet Spinning - Sailah, Illah; Fahma, Farah; Sihite, Ray Einstein Manuel (Trends in Sciences, 2022)
Cellulose as an abundantly available natural polymer can be utilized as an environmentally friendly filament material through combination with polyvinyl alcohol (PVA) and alginate. The study on cellulose/PVA/alginate composite as filament material haven not been widely reported and the effects of parameter process on the resulting filament properties still have room to be explored further. Therefore, this study focused on the effect of CaCl2 and cellulose concentration on the cellulose/PVA/alginate filaments’ thermal and mechanical properties. In this study, isolated cellulose from Oil Palm Empty Fruit Bunches (OPEFBs) was used as a reinforcement agent in filament production with PVA and alginate as a matrix by wet spinning in a CaCl2 solution as the coagulant solvent. The prepared dopes of cellulose/PVA/alginate at 5, 10 and 15 % cellulose concentration were spun using a syringe pump into 5 and 13 % CaCl2 coagulation bath. Subsequently, the resulting filaments’ mechanical and thermal properties were tested. The crystallinity and thermal stability of the filaments coagulated in 13 % CaCl2 were higher than those of in 5 % CaCl2. However, the tensile strength of the filament produced showed just the opposite. Cellulose concentration increase resulted in filament with improved thermal stability and tensile strength, and higher crystallinity. Concisely, higher CaCl2 and cellulose concentration enhanced the filament thermal properties but higher CaCl2 concentration led to filament mechanical property depression contrast to cellulose which higher concentration led to mechanical property increase. Filament has potential application in 3D printing for various application, especially filament with biodegradable, biocompatible, and enhanced mechanical property is potential for particular application such as biomedical applications as a surgical thread or biodegradable scaffold. HIGHLIGHTS Cellulose as an abundantly available natural polymer can be utilized as an environmentally friendly filament material through combination with polyvinyl alcohol (PVA) and alginate Isolated cellulose from Oil Palm Empty Fruit Bunches (OPEFBs) was used as a reinforcement agent in filament production with PVA and alginate as a matrix by wet spinning in a CaCl2 solution as the coagulant solvent Cellulose concentration increase resulted in filament with improved thermal stability and tensile strength, and higher crystallinity GRAPHICAL ABSTRACT